Dispersion relation and instability for an anisotropic nonuniform flowing plasma. (1st December 2022) - Lee, Min Uk; Yun, Gunsu S; Ji, Jeong-Young
Abstract: A generalized formula for wave instability is developed for an anisotropic nonuniform plasma with finite flows and temperatures. Six-moment fluid equations are solved to give the analytic expression for wave instability in arbitrarily nonuniform plasmas. The analytic formula explicitly states the dependence of wave instability on the nonuniformities of number density, flow velocity, and anisotropic or isotropic pressure. The accuracy of the formalism is verified by a numerical calculation of implicit dispersion relations in complex Fourier space. The analysis shows that nonuniformity plays a critical role in plasma instability, while the flow velocity and anisotropic pressures determine the growth rate of the instability. The instability diagram and associated instability criterion for anisotropy-driven instability are introduced as applications of the formalism.